Quadruple helix engagement: Reviews on Syariah Fintech based SMEs digitalization readiness - Okfalisa, Okfalisa; Mahyarni, Mahyarni; Anggraini, Wresni; Saeed, Faisal; Moshood, Taofeeq Durojaye; Saktioto, Saktioto (Institute of Advanced Engineering and Science, 2022)
The development of Syariah Financial Technology (Fintech) after Covid-19 has experienced significant fluctuations in affecting the country’s economy. The importance of the role of Financial Transactions in the digitalization readiness of SMEs makes a considerable contribution to the use of Financial Technology as an effort to maintain the sustainability of SMEs. Identification of the involvement of the quadruple Helix (government, investors, academics, and communities) in maintaining the financial stability of SMEs through Syariah Fintech emerged as new challenges and opportunities in improving the economy after Covid 19 in Indonesia. Therefore, a systematic literature review investigation regarding how to utilize Syariah fintech products adjusted to the degree of digitization is required to help SMEs’ sustainability and explore the role of the quadruple Helix in pursuing this success. We identified 110 papers published on Syariah Fintech for SMEs, SMEs Digitalization Readiness, and The Role of Quadruple Helix between 2003-2021 with 87 specifications from Scopus journals and 23 from proceedings conferences. The analysis was performed using Atlas. Ti 9 Software Packages on the above topic by limiting the discussion to inclusion and exclusion criteria. The literature review found a lack of study about the evaluation of Quadruple Helix Engagement for Syariah Fintech Based SMEs Digitalization Readiness. Thus, it needs to enhance a new Syariah fintech quadruple helix recommendation focusing on the SMEs’ digital readiness assessment to increase the utilization of proper Syariah fintech products for SMEs.